Investigasi Kemampuan Pembuktian Matematis Mahasiswa Calon Guru Melalui Pendekatan Pembelajaran Kooperatif - Kesumawati, Nila; Lusiana, Lusiana; Fuadiah, Nyiayu Fahriza (Edumatica : Jurnal Pendidikan Matematika, 2026)
The research investigates pre-service teachers’ ability to create mathematical proofs through cooperative learning, as this skill becomes essential in university mathematics education. The research used a mixed-methods survey design to study 24 students who attended the Mathematics Education program at Universitas PGRI Palembang. Data was collected by a questionnaire, a mathematical proof test, and in-depth interviews. Data analysed descriptively. The results showed that most students were in the medium category of mathematical proof ability using a cooperative learning approach, with smaller proportions in the high and low categories. The investigation concluded that students with high mathematical proof ability demonstrated the ability to implement the five Mathematical Proof Indicators (IPMs) in constructing logical and systematic arguments and using mathematical representations appropriately. Students with moderate mathematical proof ability had difficulty with IPMc (third IPM) and IPMd (fourth IPM), while students with low mathematical proof ability had difficulty with almost all IPMs. The analysis of the investigation results indicates that strategies for conducting mathematical proofs require cooperative learning support to facilitate understanding of the concepts required for proofs and collaboration, and recommends its application in mathematics learning in higher education.